Abortion’s Impact on Heidelberg Dairy Cow Milk Output, Wellness, And Reproductive Performance: A Systematic Review - Girija Shankar Sahoo, Alisha Sikri, Ramkumar Krishnamoorthy (Revista Electronica de Veterinaria, 2024)
A vital part of the world’s food supply is the dairy business, where the productivity and health of dairy cows are essential to the production of milk throughout time. The purpose of this systematic study is to look at the way abortion affects the reproductive health, milk production and general well-being of Heidelberg dairy cows. Numerous reasons, such as dietary deficits, environmental stresses and infectious illnesses, can lead to abortion episodes in dairy cows. Abortion, which is the natural ending of pregnancy between 42 and 260 days, affects the reproductive success, viability of herds and milk production, all of which have a substantial financial influence on dairy producers. The abortion records were divided into two categories: 1) new abortions (NLA) and 2) rebreeding abortions (RA). Examining the long-term consequences on reproductive capacity, overall measures of cow health and the physiological implications on milk production, the study dives into the subject. We look at how variables like breed, season, age and parity affect abortion rates. The current findings indicate that milk production dropped in cows with abortions that were categorized as NLA or RA. The results show that the abortion rate is 3.77 percent, with some variation by breed and season. The research highlights how crucial it is to understand these intricate interactions to maintain reproductive health in dairy herds efficiently. This information helps to reduce the financial losses brought by abortion incidents while enhancing the sustainability and effectiveness of dairy production.